Propuesta para la Implementación de actividades agroturísticas en la finca “Casa del Río”, comunidad El Cristal, parroquia Alto Tambo, cantón San Lorenzo, provincia de Esmeraldas - Sierra Arias, Camila Salomé (2024)
The proposed decision to implement “Agrotourism Activities” on the Casa del Río farm aims to directly link tourism with agriculture, where the tourist experientially experiences agrotourism and activities in conjunction with nature, which seeks to promote a greater connection. and harmony with tourists. In order to put this proposal into operation, it is necessary to apply a field study on the main topic of the proposal, which is agrotourism, from which the importance of each activity in our ecosystem is clear. This study proposes to analyze and develop strategies for the potential of local agricultural activities, promoting the appreciation of agriculture and respect for the environment, with economic benefits for the community. The methodology carried out is based on two qualitative and quantitative approaches, with a mixed investigation\; of three research methods: inductive, analytical and deductive\; In addition, three research techniques were used: field observation, interviews and surveys. It was applied to the active population of Barra, representing 48% of the province of Imbabura in which this population was used to identify the profile of the tourist in which the Google Form tool was used. In addition, the conditions of the farm were evaluated in collaboration with the farm owner The results obtained pertinent information about the current situation of the farm that houses the activities and services, in addition to the reason why tourists visit the community. In this way, strategies were established to strengthen agricultural tourism, concluding that agrotourism in the Cristal community will develop and strengthen over time.